“Migración Internacional de retorno y desarrollo de emprendimientos en el cantón Riobamba-ecuador”. - Álvarez Verdezoto, María José (2017)
The purpose of this research is evaluate the potentials of the international return migration in the development of entrepreneurship in Riobamba-Ecuador. It is a descriptive research because analyzing the returned migrants’ reality shows their actual situation and it becomes in a key indicator to identify the need to start up entrepreneurship in Riobamba. The research considers three fundamental aspects: a) situational diagnosis of international return migration and its potential for the development of entrepreneurship, b) Public policies implemented for international migration and development of entrepreneurship and c) Proposal to encourage the development of entrepreneurship. Through the surveys, information was collected from primary sources to determine the entrepreneurship; the sample was 285 returned migrants’ surveyed. On the other hand, the variables and determinants for the development of entrepreneurship in Riobamba were identified. An important indicator for the institutional commitment to the development of entrepreneurship is that 56% of the returned migrants have a positive attitude and aptitude toward entrepreneurship. Finally, an entrepreneurship guide is presented to encourage the development of entrepreneurship in Riobamba.